Association of Stress with Prevalence of TMJ Dysfunction in Undergraduate Dental Students - Ranjana Garg; Kevin Chee Pheng Neo; Jing Yu Lee; Mei Kei leong; Joshua Kim Chwen Ting; Donni Sonjaya (TALENTA, 2023)
Temporomandibular joint disorder (TMD) refers to persistent medical conditions that affect the temporomandibular joint (TMJ) and related structures. Studies showed that stress was closely linked to the development of TMD. Furthermore, healthcare students are particularly susceptible to stress compared to the general population. This can have a negative impact on their quality of life and mental health during their training. The increased prevalence of TMD has also been reported among the same cohort of the population. However, there is a lack of literature published highlighting the prevalence of TMD and their association with increased levels of stress in dental students. This study aims to explore whether increased stress levels are associated with the prevalence of TMD in undergraduate dental students. A total of 218 dental students participated. Two online self-reported questionnaires consisted of structured case history on past medical and dental history with a Fonseca Amnestic Index (FAI) questionnaire used to identify the prevalence of TMD and DESS questionnaire for stress prediction were used. Data were analyzed using SPSS version 22 with a p-value less than 0.05. It was reported that about 48% of students had various TMD with no significant association found between the year of study and gender. However, a significant association was reported between stress gender. A positive correlation was also found between stress and TMD among participants. This study revealed a significant association between stress and the prevalence of TMD in undergraduate dental students. Educational institutions must adopt coping strategies to help trainees manage their psychological stress, which could reduce the incidence of TMD.